Development of composite ceramic/polymeric hollow fibre membrane for water separation at low pressure and ambient temperature - Raffi, Amirul Afiat; Yusof, Noor Fadilah; Othman, Mohd Hafiz Dzarfan; Jaafar, Juhana; Ismail, Ahmad Fauzi; Abas, Khairul Hamimah; Muhamad Sidek, Mohd Akhmal; Abas, Mohd Firdaus; Yahaya, Nur Zhatul Shima; Rahman, Mukhlis A. (Elsevier, 2024)
This study proposed an enhanced water purification separation that was carried out at ambient temperature and low-pressure system. ZnO and PVA layers were deposited on the outer surface of Al2O3 hollow fibre membrane, and this composite membrane was used to separate synthetic salt solutions with a concentration of 40,000 ppm. The salt solution was introduced on the outer surface of PVA–ZnO–Al2O3 hollow fibre membrane, and distilled water was flowed through the lumen as draw solution. The PVA–ZnO–Al2O3 hollow fibre membrane showed a water flux of 25.70 kg m2 h−1 with 93.9 NaCl rejection. Al2O3 hollow fibre used in this work possessed asymmetric structure with permeability of 11.6 mD and was identified as a medium that cause a significant pressure drop within the separation system. A considerable pressure drop occurred in the porous region of the ceramic hollow fibre, causing water to vaporise. This phenomenon resulted in water evaporation at the interface between the dense sponge-like region of Al2O3 hollow fibre and PVA–ZnO membrane, thus created a positive flux for enhanced salt separation.